Energy supply during cyclist muscular activity - Kolumbet, A. N.; Natroshvili, S. G.; Chernovsky, S. M. (Journal of Physical Education and Sport, 2018)
The paper discusses the studies of energy expenditure dynamics in cyclists during performance of maximal muscular work of relative power. Fourteen athletes of the I category aged 16 years participated in the studies. During the main study, each athlete was asked to perform maximal load with voluntary distribution of efforts within 15 minutes in order to achieve maximal efficiency. Athletes performed this exercise 13 times, but only one load was used up to the end. In all other cases, work was interrupted after an unknown time for the subject since the beginning of the exercise. Interruptions were made after 30 s, 1, 1,5, 2, 2,5, 3, 4, 5, 7, 8, 10, 13 and 14 min. of work. Loads were performed in accordance with the established procedure with a sufficient rest interval within 4 days. The intensity of initial work was proved to be dependent on the power and the velocity of phosphagen and lactacid systems.